Apprendre à motiver aux futurs enseignants d’éducation physique - Stéphanie Girard; Audrey-Anne de Guise; Maude Boulanger (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Supporting student motivation is an important issue for (future) physical education (PE) teachers. However, the Reference framework for professional competencies for teachers (Minister of Education, 2020) emphasize the importance of providing teachers with resources in this regard. In order to collect students’ perceptions of what is taught to them in teacher training to learn how to support student motivation, this study aims to identify the content taught in teacher training about supporting student motivation, describe the teaching methods used to teach this content, and identify the strengths and areas for improvement in pre-service teachers' point of view. A total of 18 pre-service PE teachers (MAge = 25 years; SD = 3.61 years; Female = 38.9%) from five Francophone universities in Quebec participated in four focus groups. The results of the qualitative analyses realized according to Boutin's (2007) indicate that motivational strategies are mainly taught in theory courses and oriented towards creating a mastery climate. Moreover, the links between motivational support and the various theoretical concepts should be made more explicit. In addition, students perceive a lack of continuity and, at times, realism between theory courses and practice opportunities. Finally, they would like to have more opportunities for practice that are closer to the reality experienced with students during their professional insertion.